Influence The Intensity of Watering Towards Growth and The Production of Pepper Plants (Capsicun frutescens L.) - Sri Yuniati; Sarfuddin Sarfuddin (JURNAL AGRIYAN: JURNAL AGROTEKNOLOGI UNIDAYAN, 2019)
This study aims to determine the effect of watering intensity on the growth and production of cayenne pepper (Capsicum frutescens L.). The research was conducted at Watumotobe Village, Kapontor district of Buton Regency on May 2018. The experimental design used in this study was a randomized Design Group (RAK) with 6 treatments and grouped into 3 groups to retrieve 18 units of experiment. The observation includes the plant's height (cm), number of leaves (blades), the amount of flower (tree-1), the amount of fruit (tree-1), and the weight of fresh fruit (g). The research results showed that the intensity of watering has effect on cayanne pepper in terms of plant height, number of fruit, and the weight of fresh fruit, however it does not have effect on the amount of leave and the amount of flower of the cayane pepper (Capsicum frustencens L.).